1995
DOI: 10.1177/036354659502300623
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Tibial Compartment Pressures During Intermittent Sequential Pneumatic Compression Therapy

Abstract: We studied the anterior tibial compartment pressures during the application of a JOBST sequential intermittent pneumatic compression device on 5 healthy human volunteers (10 legs). Intracompartmental pressures were measured using a slit catheter. The measurements of interstitial pressures were highest at maximal calf inflation, and pressures were increased for approximately 120 seconds during each cycle. Pressure measurements in the inflated pressure sleeve varied less than 10% with the measured anterior tibia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Similarly, repeated cycling of a non‐invasive blood pressure cuff [43] and prolonged inflation of antishock trousers [44] have both led to compartment syndrome, confirming that external compression, particularly in the presence of hypotension, will compromise local blood flow. The elastic stocking can produce external pressures ≥ 25 mmHg [45–47] and result in a decrease in skin oxygen tension in the supine position [48]. Although not all the compression from the elastic stocking will be transmitted to the muscle compartments, this will have an additive effect to the other factors compromising local blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, repeated cycling of a non‐invasive blood pressure cuff [43] and prolonged inflation of antishock trousers [44] have both led to compartment syndrome, confirming that external compression, particularly in the presence of hypotension, will compromise local blood flow. The elastic stocking can produce external pressures ≥ 25 mmHg [45–47] and result in a decrease in skin oxygen tension in the supine position [48]. Although not all the compression from the elastic stocking will be transmitted to the muscle compartments, this will have an additive effect to the other factors compromising local blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombo‐embolic deterrent stockings (TEDS) reduce the risk of venous thrombo‐embolism (VTE) by exerting a sustained pressure of 25 mmHg on the lower limbs 33,34 . Intermittent pneumatic compression devices (ICDs) instead apply a higher pressure of 40 mmHg – and intermittently for 12 seconds per minute 35 . Although the National Institute for Health and Care Excellence (NICE) advocates the use of either – or both – for intraoperative VTE risk reduction, it has been suggested that perhaps a higher risk of WLCS exists with TEDs 33,36–38 .…”
Section: ‘Well‐leg’ Compartment Syndromementioning
confidence: 99%
“…Antiembolism/thromboembolism deterrent (TED) stockings generate a constant pressure of at least 25 mmHg, whereas intermittent pneumatic compression devices produce an intermittent pressure of approximately 40 mmHg for 12 s each minute. As the risk of compartment syndrome increases at pressures above 30 mmHg, the application of antiembolism stockings and intermittent pneumatic compression devices could increase the risk of a patient developing compartment syndrome.…”
Section: Risk Factors and Preventionmentioning
confidence: 99%